Effectiveness of rehabilitation treatment for bone metastasis patients without surgical intervention: A propensity score matching analysis - Ryo Yoshikawa; Yasumitsu Fujii; Ryoga Kashima; Wataru Saho; Risa Harada; Daisuke Makiura; Katsuya Fujiwara; Junichiro Inoue; Yoshiki Takeoka; Ryoko Sawada; Naomasa Fukase; Keisuke Oe; et al. (Journal of Bone Oncology)
Evidence regarding the effectiveness of rehabilitation treatments in patients with bone metastases remains limited. This study evaluated the implementation and effectiveness of rehabilitation in patients with bone metastases who did not undergo surgery. This retrospective study included 200 patients with nonsurgically treated bone metastases at our institution. The patients were categorized into a rehabilitation group (R group, n = 61) and a non-rehabilitation group (N group, n = 139). Over the course of one month, we compared activities of daily living (ADL), assessed using the Barthel Index (BI), quality of life (QOL), measured using the EuroQoL-5 Dimension (EQ-5D), and demographic and clinical characteristics. Propensity score matching was conducted to minimize selection bias. After matching, 31 patients in each group were included in the analysis. No statistically significant differences were observed in baseline BI and EQ-5D scores between the two groups. In the R group, BI improved significantly from 80 (interquartile range [IQR]: 60–100) to 90 (IQR: 70–100), and EQ-5D improved from 0.444 (IQR: 0.282–0.608) to 0.608 (IQR: 0.533–0.768). In contrast, no improvements were observed in either score in the N group. Chemotherapy was identified as a significant factor associated with improvements in BI (odds ratio 4.03) and EQ-5D (odds ratio 5.29). Rehabilitation may be a valuable treatment option for nonsurgically treated patients with bone metastases, warranting further validation in prospective studies.